2016
DOI: 10.1007/s00296-016-3475-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of death in systemic sclerosis patients: a single center registry report from Iran

Abstract: The aims of the study were to determine prognostic factors for survival and causes of death in a cohort of patients with systemic sclerosis (SSc). This was a cohort study of SSc patients in single rheumatologic center from January 1998 to August 2012. They fulfilled the American College of Rheumatology classification criteria for SSc or had calcinosis Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasia or sine sclerosis. Causes of death were classified as SSc related and non-SSc related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…With regards to the correlation of these autoantibodies with disease prognosis, it seems that more Iranian SSc patients have a poor prognosis. However, a study has reported that survival rates in Iranian SSc patients are 93% and 83% at 5 and 10 years from diagnosis, respectively [36], which is not different from other countries [37][38][39][40][41].…”
Section: Discussion_____________________________mentioning
confidence: 82%
“…With regards to the correlation of these autoantibodies with disease prognosis, it seems that more Iranian SSc patients have a poor prognosis. However, a study has reported that survival rates in Iranian SSc patients are 93% and 83% at 5 and 10 years from diagnosis, respectively [36], which is not different from other countries [37][38][39][40][41].…”
Section: Discussion_____________________________mentioning
confidence: 82%
“…Telangiectasia was slightly associated with a higher mortality in our study population. In contrast, Poormoghim et al [51] reported a non-significant, yet elevated HR of 1.44 in a smaller cohort of Iranian patients. An increased number of telangiectasia has been suggested to be a clinical marker of microvascular disease in SSc and is associated with an increased risk of PAH [59].…”
Section: Discussionmentioning
confidence: 84%
“…The number of articles included in this meta‐analysis is low, few studies focused on the association between DUs and mortality, and data extraction depended on the quality of the studies. Two studies included were published more than twenty years ago, and four studies had a short follow‐up of <5 years, suggesting a potential bias. Despite these limitations, however, this meta‐analysis based on two exhaustive research strategies reveals for the first time an increased risk of mortality in SSc patients with DUs.…”
Section: Discussionmentioning
confidence: 99%